Mesoscale simulations of saturated flow boiling heat transfer in a horizontal microchannel. (17th August 2020) - Wang, Haoyuan; Lou, Qin; Li, Ling
Abstract: The bubble dynamics and their effects on flow boiling heat transfer in a horizontal channel are investigated under constant wall temperature and constant wall heat flux conditions. It is found that both the bubble departure time and departure diameter decrease with increasing the inertial force for all the considered heating modes. Moreover, the bubble departs from the heater with a residual for the constant wall temperature condition so the heat transfer efficiency for the constant wall temperature condition depends mainly on the bubble growth rate and the vapor thickness. While for the constant heat flux condition, the bubble slides away from the heater accompany with waiting periods. So the heat transfer performance for this condition is mainly affected by the growth and waiting times. Besides, the results also show there were two contradictory trends of heat transfer efficiency under different wettabilities for the considered heat modes.